The prevalence and real‐world therapeutic analysis of Chinese patients with KRAS‐Mutant Non‐Small Cell lung cancer. (8th April 2022) - Chen, Hanxiao; Huang, Dingzhi; Lin, Gen; Yang, Xue; Zhuo, Minglei; Chi, Yujia; Zhai, Xiaoyu; Jia, Bo; Wang, Jingjing; Wang, Yuyan; Li, Jianjie; An, Tongtong; et al.
Abstract: Objective: Kirsten rat sarcoma viral oncogene homolog (KRAS) is an important driver gene of non‐small cell lung cancer (NSCLC). Despite a rapid progress achieved in the targeted therapy, chemotherapy remains the standard treatment option for patients with KRAS‐mutant NSCLC. This study aimed to assess real‐world data of Chinese patients with KRAS‐mutant NSCLC undergoing chemotherapy and/or immunotherapy. Methods: KRAS mutational status was analyzed using next‐generation sequencing of 150, 327 NSCLC patients from the Lung Cancer Big Data Precise Treatment Collaboration Group (LANDSCAPE) project (Cohort I). Treatment data were collected and analyzed retrospectively from 4348 NSCLC patients who were admitted to the Peking University Cancer Hospital and Institute between January 2009 and October 2020 (Cohort II). Results: In Cohort I, 18, 224 patients were detected with KRAS mutations (12.1%) of whom G12C (29.6%) was the most frequent subtype, followed by G12D (18.1%) and G12V (17.5%). In case of concomitant mutations, TP53 had the highest incidence of 33.6%, followed by EGFR (11.6%), STK11 (10.4%), KEAP1(6.2%), and CDKN2A (6.0%). Cohort II included 497 patients (11.4%) with KRAS mutations. In the first‐line chemotherapeutic analysis of Cohort II, patients benefited more from the pemetrexed/platinum (PP) regimen than the gemcitabine/platinum (GP) or taxanes/platinum (TP) regimen (median progression‐free survival [PFS], 6.4 vs. 4.9 vs. 5.6 months, hazard ratio [HR] = 0.65, 95% confidence interval [CI] 0.48–0.88, p  = 0.033 and HR = 0.69, 95% CI 0.47–1.00, p  = 0.05, respectively), with no significant difference when combined with bevacizumab. Regarding patients who received immune checkpoint inhibitors (ICIs), the objective response rate was 26% for a median PFS of 9.6 months (95% CI 6.16–13.03). Patients who received ICIs combined with chemotherapy had a significantly longer survival than monotherapy (median PFS, 13.9 vs. 5.2 months, HR = 0.59, 95% CI 0.35–0.99, p  = 0.049). Conclusion: KRAS is an important driver gene in NSCLC, compromising 12.1% in this study, and G12C was noted as the most common subtype. Patients with KRAS‐mutant NSCLC could benefit from pemetrexed‐based chemotherapy and ICIs. Abstract : This was the first study to analyze the treatment of KRAS‐mutant NSCLC patients in China, including chemotherapy and immunotherapy. Overall, the rate of KRAS mutation was approximately 11.4%‐12.1% in the Chinese patients with KRAS‐mutant NSCLC, and G12C was found as the most common subtype. In chemotherapy, patients with KRAS mutations could benefit more from the pemetrexed‐based regimen, regardless of mutational sites. ICIs may be a fruitful treatment modality for patients with KRAS‐mutant NSCLC, especially combined with chemotherapy.